Local Information and Firm Expectations about Aggregates - Jonas Dovern; Lena Sophia Müller; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2022)
Using new survey data on quantitative growth expectations of firms in Germany, we show that firms resort to local information when forming expectations about aggregate growth. Firms extrapolate from the economic situation in their county, industry growth and their individual business situation. The effect is particularly strong for small firms and explains part of the high expectation dispersion across firms. Furthermore, we show that growth expectations are correlated with employment and investment decisions of firms, highlighting that differences in expectations do indeed seem to lead to differences in actual firm decisions. Our results confirm predictions of theoretical models with rational inattention.
Keywords: D84; E20; E32; 330; GDP expectations; expectation heterogeneity; disagreement; rational inattention; ifo business tendency survey